2012
DOI: 10.1152/ajprenal.00277.2012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glomerulotubular balance. II. Impact of angiotensin II on flow-dependent transport

Abstract: Underlying glomerulotubular balance (GTB) is the impact of axial flow to regulate Na ϩ and HCO 3 Ϫ transport by modulating Na ϩ -H ϩ exchanger 3 (NHE3) and H-ATPase activity. It is not known whether the cascade of events following a change in flow relies on local angiotensin (ANG II) generation or receptor availability. Mouse tubules were microperfused in vitro at flows of 5 and 20 nl/min, and net fluid (Jv) and HCO 3 Ϫ (JHCO3) absorption and cell height were measured. Na ϩ (JNa) and Cl Ϫ (JCl) absorption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 60 publications
5
29
0
Order By: Relevance
“…We found that blocking the AT 1 receptor by losartan reduced absolute Na ϩ and HCO 3 Ϫ absorption at both low and high flows, but did not affect fractional flowstimulated transport. Compared with WT control, in AT 1a KO mouse tubules, 53% of flow-stimulated Na ϩ absorption was abolished, but flow-stimulated HCO 3 Ϫ absorption was retained at similar levels. The remaining flow-stimulated HCO 3 Ϫ absorption was eliminated by the H-ATPase inhibitor bafilomycin.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…We found that blocking the AT 1 receptor by losartan reduced absolute Na ϩ and HCO 3 Ϫ absorption at both low and high flows, but did not affect fractional flowstimulated transport. Compared with WT control, in AT 1a KO mouse tubules, 53% of flow-stimulated Na ϩ absorption was abolished, but flow-stimulated HCO 3 Ϫ absorption was retained at similar levels. The remaining flow-stimulated HCO 3 Ϫ absorption was eliminated by the H-ATPase inhibitor bafilomycin.…”
mentioning
confidence: 75%
“…We also found that NHE3 expression at the protein level was reduced in AT 1a KO mice kidneys. These results indicate that the AT 1 receptor is important in maximizing the NHE activity activated by flow; however, it is not critical for the flow-stimulated HCO 3 Ϫ transport, which still exists when the inhibitors are present or when the AT 1a receptor is knocked out (3).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The cycling conditions for all genes were: preincubation at 95°C for 10 min, followed by 40 cycles at 94°C for 15 s and 60°C for 60 s. The final mRNA abundance of each gene was normalized to the abundance of an endogeneous gene, Cyclophilin A, using the DDC T method (2 ϪDDCT ). Fold-change in the gene expression was calculated (15). The primers used in this study were listed in Table 1.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%